STRATEGI ADAPTASI GURU PAI DALAM MENGHADAPI DISRUPSI DIGITAL: PELUANG DAN HAMBATAN - Hakim, Luqmanul (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Digital disruption has fundamentally transformed the educational landscape, demanding adaptation from various stakeholders, including islamic education teachers. This article aims to analyze the adaptation strategies of islamic education teachers in facing digital disruption, identify emerging opportunities, and examine the obstacles encountered. Employing a literature review method, this research compiles and analyzes information from various scholarly sources related to digital disruption in education, the role of islamic education teachers, and learning strategies in the digital era. The findings indicate that Islamic Education teachers have significant opportunities to enhance the quality of learning through the utilization of digital technology, such as e-learning platforms, social media, and online learning resources. However, there are also obstacles, including a lack of digital competency, infrastructure limitations, and challenges in maintaining religious values amidst the influx of digital information. This article recommends the necessity of improving continuous professional training and development for islamic education steachers, providing adequate infrastructure, and developing a curriculum that is adaptive to technological advancements.